Big Business and National Governments: Reshaping the Compact in a Globalizing Economy - Vernon, Raymond (Journal of International Business Studies, 2001)
This paper was written by Raymond Vernon for the conference, “Mapping the Multinationals,” organized by Bruce Mazlish and Alfred Chandler in October 1999. Professor Vernon died on August 26, 1999, at the age of 85, before the paper was finished and presented. It was the last paper he wrote. We are pleased to be able to publish it posthumously in this symposium, with the permission of his daughter Heidi Vernon. The paper was subject to minimal copyediting by the editor of JIBS.